ХААНТ ОРОС УЛСЫН САНХҮҮГИЙН ЗӨВЛӨХ ТҮШМЭЛТЭЙ БАЙГУУЛСАН ГЭРЭЭНИЙ ТУХАЙД - Г. Цэнджав (Politology, 2023)
The beginning of XX century, the Russian foreign policy to became active in the Far East such as Outer Mongolia. In that time, Outer Mongolia declared own independence from Qing Dynasty and some aids had been supported by the Russia, which was encouraged by concept of the Russian foreign policy. Therefore, the Russian government implemented the action of the economic protectorate program in Mongolia, was searching natural recourse and was forcing out the Chinese traders from the country by the Russian consulter. Хураангуй: Хаант Оросын гадаад бодлого нь ХХ зууны эхэн үеэс Алс дорнодод хандах үйл ажиллагаагаа улам идэвхжүүлж,улмаар Ар Монголд нөлөөлөх талаар бодиттой ажлуудыг хийж эхэлсэн билээ.Тухайн цаг үед Монгол нь туурга тусгаар улсаа тунхаглаж, Хаант Орос улсыг өөрийн өмөг түшгээ хэмээн үзэж, мөнгө санхүүгийн болон зэр зэвсгийн тусламжийг удаа дараа хүсэх болсон.